A facile and robust non-natural three enzyme biocatalytic cascade based on Escherichia coli surface assembly for fatty alcohol production. (1st February 2019) - Xu, Yun; Li, Fei; Yang, Kaixin; Qiao, Yangge; Yan, Yunjun; Yan, Jinyong
Graphical abstract: Highlights: Surface assembly of three enzymes as non-natural cascade for alcohol production. Genetically customizing ratio and positional arrangement of each enzyme. Significant proximity effect exhibited in multiple enzyme complex. Improved stability in various unfavorable environments. Abstract: Fatty alcohol is considered as a promising clean fuel alternative to fossil fuel. In this study, we developed a facile and robust multiple enzyme complex of lipase (LIP), carboxylic acid reductase (CAR) and aldehyde reductase (AHR) based on cohesin-dockerin specific interaction and E. coli -ice nucleation protein (INP) surface assembly for highly efficient conversion of triacylglycerols (TAGs) to fatty alcohols. The proximity effect, customized ratio and positional arrangement of the three enzymes were readily genetically generated. The optimized cell associated three enzyme complex gave 73% of conversion yield, and showed significantly improved stability in higher temperature, acidic/alkaline environments, polar organic solvents, high concentration of substrate, and good recyclability in successive biotransformations. The three enzyme complex provides an efficient non-natural synthetic cascade route for fatty alcohol bioproduction alternative to complex de novo biosynthesis route.